Enhancing the Ability of 'Spatial Nets' through Outdoor Learning-Based on Traditional Game 'Baju Simi' - Yumiati, Yumiati; Haji, Saleh; Antasari, Melisa (Universitas Muhammadiyah Mataram, 2023)
Traditional games are rooted in a regional culture with educational values that are important for future generations. These educational values, among others, contain various mathematical concepts (geometry). This study aims to improve students' Spatial Nets ability through the outdoor learning-based traditional game 'Baju Simi.' The type of research used is classroom action research. The research subjects were 20 students of class VI Sekolah Dasar Negeri 98 Kaur, Bengkulu. The study was conducted in the Even Semester 2022/2023. The instrument used is a test on 'Spatial Nets' with as many as ten essay questions. In addition, it also uses questionnaire instruments, observation guidelines, and interview guidelines. Data were analyzed qualitatively. The results obtained are as follows: (1) In Cycle 1, there was an increase in the ability of 'spatial nets' by 0.21 with low pre-test and post-test scores of 45 and 56.5, respectively; and (2) In Cycle 2, there was an increase in the ability of 'spatial nets' by 0.36 with an average pre-test and post-test score of 53 and 70.25 respectively. As many as 92% of students can understand the meaning of space-building nets correctly. 87% and 82% of students can precisely define the webs of cubes and blocks. This study implies that traditional games can be used as a medium and source of learning mathematics (geometry) in elementary schools so that students are highly motivated (4.2 on a scale of 5) in learning mathematics (geometry).